The effects of mannose capped lipoarabinomannan on dendritic cell function - Lee, Eric John, author; Gonzalez-Juarrero, Mercedes, advisor; Schenkel, Alan, committee member; Chen, Chaoping, committee member (Colorado State University. Libraries, 2009)
M. tuberculosis is one of the leading causes of death due to infectious disease in the world. While the majority of people are capable of controlling the initial infection, many progress to a latent stage of disease where the M. tuberculosis bacilli persist for long periods of time within the host. The M. tuberculosis cell wall lipoglycan mannose capped lipoarabinomannan (ManLAM) has been characterized as one of the immunomodulatory factors associated with the bacteria [3-5]. ManLAM interacts with dendritic cells (DCs) via DC-SIGN, mannose receptors and to a lesser extent TLR-2 [6-8]. Thus we set out to examine the effects that ManLAM has on DCs both in vitro and in vivo. ManLAM treatment of bone marrow derived DCs (BMDCs) prevents their phenotypic maturation reduces the expression of MHC class II and CD1d. BMDCs stimulated with ManLAM also exhibit altered phagocytic capacity and the inability to stimulate naïve CD4+ T-cell proliferation.
Department Head: Paul J. Laybourn.